Cytotoxicity studies of tert-butylhydroperoxide on HEPG2 and WRL68 cell lines / Haniff Mohd Nawi - Mohd Nawi, Haniff (2008)
Antioxidants are important to protect cells from the damage caused by the ROS which lead to many diseases such as cancer, coronary heart disease, stroke, rheumatoid arthritis, and diabetes mellitus as well as in degenerative processes associated with aging. This study design is to obtain the IC50 of tert-butylhydroperoxide on WRL68 and HepG2 cells. From this research that has been done on both of these cells then, could be a model for others researcher to use in their experiment to investigate new antioxidant and the cytoprotective effect of new substances. tert-Butylhydroperoxide (t-BHP) is an organic lipid hydroperoxide analogue, which is commonly used as a pro-oxidant for evaluating mechanisms involving oxidative stress in cells and tissues. HepG2 and WRL68 cells are exposed to the t-BHP at various concentrations (1000 µM, 100 µM, 10 µMand 1 µM). The viability of the cells was accessed using MTS assay and LOH assay. The control of the study was done using 0 µM oft-BHP and 1 % Triton-X. The IC5o values for HepG2 and WRL68 were 36.18 ± 1.21 µM and 39.23 ± 14.75 µM, respectively for the MTS. LOH assay gave the IC50 HepG2 and WRL68 were 26.25 ± 3.34 µMand 3.26 ± 0.63 µM, respectively. It is concluded that, HepG2 and WRL68 are equally susceptible to death due to t-BHP. However, WRL68 is more susceptible as compared to HepG2.